Maybe you don't want to retire - Armstrong, Frank, III (FT Press Delivers elements., 2011)
This Element is an excerpt from Save Your Retirement: What to Do If You Haven't Saved Enough or If Your Investments Were Devastated by the Market Meltdown (9780137029006) by Frank Armstrong III and Paul B. Brown. Available in print and digital formats. Think the unthinkable! Why you simply might not want to retire (it's not just about the money). Could it be that the financial shortfall you are experiencing-due to the financial meltdown, your inability to save enough, or some other factor-is actually a good thing? It could be if it forces you to think about the following sentence: "Maybe I don't want to retire." It's not as strange a thought as it may first sound....